Evaluating tourism sustainability in Tioman Island, Malaysia - Chia, Kei Wei (2011)
This thesis seeks to identify the sustainable island tourism problems faced by Tioman Island and to determine the sustainable status of the island from the perspectives of four stakeholder groups (residents, business operators, tourists, and government officers). A mixed methodology approach combining both quantitative and qualitative approach was adopted. The qualitative interviews uncovered 15 problems faced by the various stakeholder groups in the island. The 15 problems identified in the interviews were then used to construct questionnaire for further analysis. From the 320 returned questionnaire survey with four stakeholder groups, it was found that there was consensus among the 4 stakeholder groups for 8 of the problems faced by Tioman Island. In addition, the stakeholder cooperation percentage scores indicated that none of the stakeholder groups tried to escape from the responsibilities to help solving the problems. It was worth noted that government officers did not push the responsibility to other stakeholders. Finally, the Sustainable Ecotourism Indicators System (SEIS) was used to assess the sustainability level of Tioman Island. The SEIS scores were revealed that the island is now at a ‘‘potential sustainable’’ stage which means that it is still potentially sustainable. This thesis broadens the literature on island tourism by adding additional two unique problems and also extends the spectrum of SEIS by incorporating additional 9 items in island destination. This thesis may help tourism planners, developers, and policy-makers to understand the current problems faced by the island so that strategies can be implemented accordingly to assess, to monitor, and to evaluate problems based on the cooperation percentage and consensus scores. Future study can be improved by conducting a longitudinal study, using Delphi technique to gain consensus opinions experts in that particular field, adding more stakeholder groups, and extending the SEIS beyond ecotourism context.